Pengaruh Net Profit Margin (NPM) Return On Asset (ROA), Return On Equity (ROA) Terhadap Nilai Perusahaan PT. Astra International TBK Tahun 2017-2021 - Inka Nabela Nabela; Yun Fitriano; Nenden Restu Hidayah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Rapid economic development and the emergence of many new companies make every company in Indonesia must have a high ability to maintain the stability of the company's sustainability and company value.The purpose of this study was to determine the effect of Net Profit Margin, Return on Assets, Return on Equity on the Company Value of PT. Astra International Tbk. Data collection was carried out by taking samples on the website www.idx.co.id and data were analyzed using descriptive statistical analysis methods, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression tests and determination tests.The results of the regression analysis show Y = 1.135 + 1.600NPM – 108.378ROA + 59.865ROE which means that the three variables have an influence on firm value. The value of the coefficient of determination is 0.536. This shows that Net Profit Margin (X1), Return on Assets (X2) and Return on Equity (X3) have an effect on Firm Value (Y) of 53.6% while the remaining 46.4% is influenced by other variables not included in this study. the results of the t test at a significance level of 0.05 explain that partially Net Profit Margin, Return on Assets and Return on Equity have a significant influence on the Company Value of PT. Astra International Tbk.